6.5=-4(-n-4)

Simple and best practice solution for 6.5=-4(-n-4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6.5=-4(-n-4) equation:


Simplifying
6.5 = -4(-1n + -4)

Reorder the terms:
6.5 = -4(-4 + -1n)
6.5 = (-4 * -4 + -1n * -4)
6.5 = (16 + 4n)

Solving
6.5 = 16 + 4n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-4n' to each side of the equation.
6.5 + -4n = 16 + 4n + -4n

Combine like terms: 4n + -4n = 0
6.5 + -4n = 16 + 0
6.5 + -4n = 16

Add '-6.5' to each side of the equation.
6.5 + -6.5 + -4n = 16 + -6.5

Combine like terms: 6.5 + -6.5 = 0.0
0.0 + -4n = 16 + -6.5
-4n = 16 + -6.5

Combine like terms: 16 + -6.5 = 9.5
-4n = 9.5

Divide each side by '-4'.
n = -2.375

Simplifying
n = -2.375

See similar equations:

| 3*(2x+2)=4*(x+8) | | 14x+2=16+7x | | 2x+13=35-10x | | 2x+.3=.2x+2.1 | | 2x^4-6x^5=12x^2-36x | | 5x-13+11x-61+7x-29=180 | | 64+4x=-1 | | 7=11m-5m | | 4x-x+3=5x+8 | | 16t^2-25=y | | 8(x+4)=174 | | 2(4x+2)=3x+5x+4 | | 5638.92-273.43= | | 8m+6(3)=56 | | 5x+6x+3=7-x | | -16+-7=17 | | (8-4i)+(2+7i)= | | 6x+6=2(x+-1)+2(2x+4) | | 80+2x+20=180 | | -5x=-5.5 | | 12(x+2)=132 | | 36,599.0697=4/3*3.14*r^3 | | 82-6x=7x-17 | | 3x+2=4(2x+1)-5x | | 144+1x=8x+2.5x | | 3c-7(10)=100 | | 7x-2(3+4x)=10 | | 14(-7x)-23=46 | | 80=2x+20 | | (cosx+2)=0 | | 23x-12=-3 | | 4(-2+3y)=40 |

Equations solver categories